The Treatment Based on Temporal Information Processing Reduces Speech Comprehension Deficits in Aphasic Subjects - Szymaszek, Aneta; Wolak, Tomasz; Szelag, Elzbieta (Frontiers in Aging Neuroscience, 2017)
Experimental studies have reported a close association between temporal information processing (TIP) and language comprehension. Brain-injured subjects with aphasia show disturbed TIP which was evidenced in elevated temporal order threshold (TOT) as compared to control subjects. The present study is aimed at improving auditory speech comprehension in aphasic subjects using a specific temporal treatment. Fourteen patients having deficits in both speech comprehension and TIP were tested. The Token Test, phoneme discrimination tests and Voice-Onset-Time Test were employed to assess speech comprehension. The TOT was measured using two 10 ms tones (400, 3000Hz) presented binaurally. The patients participated in eight 45-minute sessions of either the specific temporal treatment (n=7) aimed at improving the perception of sequencing abilities, or in a non-temporal control treatment (n=7) on volume discrimination. The temporal treatment yielded an improvement in TIP. Moreover, a transfer of improvement from the time domain to the language domain was observed. The control treatment did not improve either TIP or speech comprehension in any of the applied tests.